Exploring the concept of pride from the perspective of Muslim women - Jan, Muhammad Tahir (2017)
In today’s fast developing and modern world, Muslim women are faced with so many challenges, especially, when it comes to their attire, faith, and pride. The Hijab, in particular, has become quite a controversial topic in recent years, putting Muslim women in spotlight about their choices of clothing. This paper discusses those factors, extracted from the review of extant literature, which tend to constitute and form pride of a Muslim woman in today’s time and age. It also highlights the role these factors play in enhancing one’s self-worth. In-depth review of the literature revealed that good and respectable job, sound education, the performance of Hajj or Umrah, and Hijab (covering of head and body) are the main sources of pride for them. Further, this study proposed a conceptual model to be considered for future empirical testing. Lastly, conclusion and direction for further research is also offered.